Interfacial heat transport in nano-carbon assemblies - Qiu, Lin; Zhang, Xiaohua; Guo, Zhixin; Li, Qingwen (Carbon (New York), 2021)
Although the individual one- and two-dimensional (1D and 2D) carbon nanostructures possess extremely high thermal conductivity, their macroscopic assemblies do not efficiently utilize it due to the larger interfacial contact thermal resistance. To improve the overall performance, the key is the interfacial structure design to provide sufficient pathways for phonon transport with a limited sacrifice or damage to the inherent thermal properties of nanomaterials. Particularly, the resonance of low-frequency lattice vibrations is the most important mechanism for the reduction of the interfacial contact thermal resistance. Based on recent theoretical and experimental studies and observations on interfacial heat transport, we review here a fourfold set of transport problems in this field: (1) low-frequency phonons in 1D and 2D nanostructures for heat transport; (2) the mechanisms of interfacial thermal transport; (3) assembly structure design towards high utilization of the thermal conductivity from individual nanostructures; and (4) recent development of thermal conductivity measurement for individual and assembled nanomaterials. [Display omitted] •Low frequency phonons play important roles in thermal transport of nano-carbons.•Interfacial thermal transport is greatly determined by interfacial phonon coupling.•Recent progresses on the thermal conductivity of nano-carbon assemblies are reviewed.•Thermal conductivity measurement strategies and their related upgrades are discussed.